NEGARA ISLAM SEBAGAI SEBUAH IDEALISME YANG HARUS BERHADAPAN DENGAN REALITAS KEHIDUPAN DI BUMI NUSANTARA - Hukom, David Arthur (JURNAL ISLAM NUSANTARA, 2019)
There is always an unfinished conversation about Nation because of the concept differences with one to another which is certainly not become an issue. However it is a problem once it is forced to be applied in an existing concept of the State. Democracy is dealing with the values of religion as one of the basic principles of the State, in this study it is Islam. Eventhough, reality shows that the religion state does not guarantee social justice for the whole people because of the disputes and even it is up to war and unfortunately permitted. However, for some people to establish religion state is an important thing. Not only individual but also political parties and mass organizations need the establishment of a state on the basis of religion. But these ideals are certainly not easy because it must be dealing with so much different context and concept that it has been set up before. This paper aims to describe that the history of religion state journey can be a consideration for the realization of an idealistic religion state in the middle of an unidealistic reality.